2017
DOI: 10.1177/0735633117692102
|View full text |Cite
|
Sign up to set email alerts
|

Using a Two-Stage System Evaluation Approach to Explore the New Adoption of an Information System in the Mobile Era

Abstract: Currently, e-learning systems are being widely used in all stages of education. However, it is difficult for school administrators to accurately assess the actual usage performance of a new system, especially when an organization wishes to update the system for users from different backgrounds using new devices such as smartphones. To allow school administrators to conduct upgrades of e-learning systems that take into consideration students' current usage conditions, this study proposed a two-stage system eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Jamshidi et al (2018) cited the retracted article under the Limitations and Future Research section. Lastly, Chen and Liu (2017) cited the retracted article in the Literature Review section and adapted the study’s questionnaire. It was observed that all these articles cited Mohammadi (2015) without acknowledging its retraction, despite the article having been retracted since 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Jamshidi et al (2018) cited the retracted article under the Limitations and Future Research section. Lastly, Chen and Liu (2017) cited the retracted article in the Literature Review section and adapted the study’s questionnaire. It was observed that all these articles cited Mohammadi (2015) without acknowledging its retraction, despite the article having been retracted since 2015.…”
Section: Resultsmentioning
confidence: 99%
“…Besides communication, smartphones in mobile learning can also function as a video recorder to record lectures (Razzaq et al (2018). The original TAM model, the behavioral intention, was affected by two perceived factors, namely, perceived ease of use and perceived usefulness, and the former also significantly affected the latter (Chen & Liu, 2017). The scholars revealed that the study replaced the original perceived variables in the TAM with perceived system use, mainly to evaluate the overall perception of e-learning system usage.…”
Section: Technology and Behaviormentioning
confidence: 99%
“…The technology infrastructure improvement in schools has increased exponentially in the past few decades. Teachers around the globe are facing challenges in providing effective teaching methods for the digital native generation (Chen & Liu, 2017; Lim, Zhao, Tondeur, Chai, & Tsai, 2013). In the 21st century, when individuals’ learning autonomy is crucial, CT has become one of the important competences (Ghanizadeh, 2017; Hwang & Chen, 2017; Kereluik, Mishra, Fahnoe, & Terry, 2013; Scott, 2015; Yang, Chuang, Li, & Tseng, 2013).…”
Section: Introductionmentioning
confidence: 99%